Prehypertension and its associated factors among type ii diabetes mellitus patients in Kelantan - Din, Noor Nazli (2024)
Background: Prehypertension is defined by systolic blood pressure ranging from 120 to139 mmHg and/or diastolic blood pressure of 80 to 89 mmHg. Type II Diabetes Mellitus (T2DM) patients with prehypertension face higher risks of cardiovascular morbidity and mortality compared to normotensive T2DM patients. However, many T2DM patients remains unaware of their prehypertensive status and the associated increased CVD risks. Objective: This study aims to determine the proportion of prehypertension and its associated factors among Type II Diabetes Mellitus patients in Kelantan for year 2022. Methodology: This cross-sectional study was conducted from December 2023 to June 2024 using secondary data from Kelantan National Diabetes Registry (NDR) clinical audit datasets for the year 2022. Data of T2DM patients who were more than 18 years old and documented not hypertensive in the registry was collected using a proforma and analysed using IBM SPSS version 28 software. Results: There were 8657 T2DM patients clinical audit datasets in Kelantan NDR for the year 2022, of which, 825 patient datasets fulfilled the study criteria and were included in the study. Descriptive and multiple logistic regression analysis were performed. The proportion of prehypertensive T2DM patients was 73.5% (606 patients) with a mean (SD) age of 55.8 (11.30) years old, majority being the female patients at 402 patients (66.3%) and of Malay ethnicity at 585 (96.5%) patients. Only 41 (6.8%) patients were smoker while 330 (54.5%) patients had dyslipidaemia. Majority of patients were overweight [254 (41.9%) patients] and obese [215 (35.5%) patients] with 370 (61.1%) patients having abnormal waist circumference. The mean (SD) of HbA1c level was 8.31% (2.21) while 87 (14.4%) patients experienced microalbuminuria. Significant association with prehypertension was found for age (aOR 1.02; 95% CI: 1.003, 1.03; p = 0.012), sex (aOR 1.54; 95% CI: 1.10, 2.15; p = 0.013) and smoking (aOR 2.19; 95% CI: 1.02, 4.73; p = 0.045) Conclusion: There was a high proportion of prehypertension among T2DM patients in Kelantan in the year 2022. Besides non-modifiable factors age and sex, smoking was significantly associated with prehypertension among T2DM patients thus highlighting the importance of smoking cessation promotion for T2DM patients to prevent the development of prehypertension.